Challenges before the information commissions under right to information act, 2005 - Kaur, Manpreet; Verma, Mohit (2008)
The Right to Information Act 2005 in Section 12 (1) and 15(1) provides for the establishment of Central Information Commission and State Information Commissions, respectively. The act empowers the Information Commissions to work as an independent body to handle appeals, complaints and monitor implementation of the Act. Problematically, however, the Information Commissions are facing numerous challenges such as environment of secrecy, untrained Public Information Officers, ambiguous provisions of Act, poor record management appointment of Chief Information Commissioners, Validity of the decisions of Information Commissions and Coordination of activities. The present study is to present the contemporary state of concerned challenges and to propose suggestion or effective and efficient implementation of this Noble Legislations. - Reproduced.
Keywords: Right to information